Culture as a mediator of climate change adaptation: Neither static nor unidirectional. (27th October 2020) - Few, Roger; Spear, Dian; Singh, Chandni; Tebboth, Mark G. L.; Davies, Julia E.; Thompson‐Hall, Mary C.
Abstract: Though there is increasing recognition of the cultural dimensions that shape climate change adaptation, our experience from working with actors engaged in adaptation policy and practice suggests that the role of culture still tends to be conceived in overly narrow and fixed terms. This is exemplified in portrayals of conservative cultural norms as stifling positive change. A growing body of research across the world indicates that the reality is seldom as simple as this—culture works in complex and variable ways, and, most importantly, is inherently dynamic. Drawing especially from research work on vulnerability and adaptation conducted in semi‐arid regions, we illustrate this argument by briefly exploring three themes—multiple knowledge systems for farming in Botswana, the dynamics of pastoralist values and livelihoods in Kenya, and the interplay of caste and livelihood choices in India. Understanding how different facets of culture such as these operate in context helps move away from viewing culture statically as a barrier or enabler, and toward a more plural and dynamic appreciation of the role of culture in adaptation. This includes recognizing the potential for factors that may be construed as barriers to become enablers. Critical, balanced engagement with cultural dimensions in both research and practice, understanding and working with these dynamic social structures, is essential if adaptation is to create meaningful and lasting change for those who need it most. This article is categorized under: Vulnerability and Adaptation to Climate Change > Values‐Based Approach to Vulnerability and Adaptation Abstract : Image created for a research exercise with pastoralist communities in northern Kenya, exploring perspectives on adaptation: in this case a change toward keeping more drought‐resistant livestock. This is one of many forms of adaptation in which it is important to interrogate assumptions about how cultural values and norms operate.